2021
DOI: 10.1002/ccd.29638
|View full text |Cite
|
Sign up to set email alerts
|

Elective versus urgent in‐hospital transcatheter aortic valve implantation

Abstract: Background Transcatheter aortic valve implantation (TAVI) is maturing as a treatment option and is now often undertaken during an unscheduled index hospital admission. The aim of this study was to look at procedural and mid‐term outcomes of patients undergoing elective versus urgent in‐hospital transcatheter aortic valve implantation. Methods We identified a total of 1,157 patients who underwent TAVI between November 2007 and November 2019 at the Sussex Cardiac Centre in the UK. We compared the demographics, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
1
15
2
Order By: Relevance
“…With regard to mortality during hospitalization and one year after TAVI, there were 7 [ 8 , 10 , 13 17 ] and 9 [ 4 , 8 , 10 , 11 , 13 , 17 ] studies describing the pertinent data, respectively. A significant difference was noted between emergent and elective TAVI on the mortality at hospitalization (emergent vs selective, HR 2.09, 95% CI [1.39 to 3.14], I 2 = 86.5%, Q test P < 0.001, Figure 4(a) ) and 1 year (HR 1.96, 95% CI [1.55 to 2.49], I 2 = 66.2%, Q test P =0.003, Figure 4(b) ) in the random effect model.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to mortality during hospitalization and one year after TAVI, there were 7 [ 8 , 10 , 13 17 ] and 9 [ 4 , 8 , 10 , 11 , 13 , 17 ] studies describing the pertinent data, respectively. A significant difference was noted between emergent and elective TAVI on the mortality at hospitalization (emergent vs selective, HR 2.09, 95% CI [1.39 to 3.14], I 2 = 86.5%, Q test P < 0.001, Figure 4(a) ) and 1 year (HR 1.96, 95% CI [1.55 to 2.49], I 2 = 66.2%, Q test P =0.003, Figure 4(b) ) in the random effect model.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that in patients with AS, hospitalization for acute decompensation is associated with poor outcomes [2,3,5], and some data point to a better prognosis in this cohort of patients if treated with SAVR (33% 5-year mortality, 23.2% HF hospitalization) compared to conservative management (75.3% 5-year mortality, 70.4% HF hospitalization), although the results are still worse than in elective procedures (17.3% 5-year mortality, 4.8% HF hospitalization) [5]. Robust data concerning TAVI outcomes in this specific population are limited, and there are discrepancies in the published studies, with most of them showing worse outcomes (mortality, acute kidney injury, bleeding, rehospitalization) [5,[11][12][13] in urgent procedures, but with few data suggesting similar results concerning mortality, hospitalization and other adverse events [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first percutaneous aortic valve was implanted in 2002, a significant evolution in TAVI technology has occurred, allowing the treatment of more patients, from low-to very-high risk [6][7][8][9][10]. Despite that, there is still some uncertainty regarding TAVI results in patients submitted to urgent procedures, with most literature suggesting that this subgroup of patients tend to have worse results, but some data pointing to similar outcomes [5,[11][12][13][14][15]. There is also a gap in the guidelines concerning aortic valve replacement in this acute setting, with only a brief recommendation for aortic balloon valvuloplasty as a bridge to TAVI or surgical aortic valve replacement (SAVR) in decompensated AS [16].…”
Section: Introductionmentioning
confidence: 99%
“…This rate of urgent/emergency TAVI was lower than that of 10-24% reported in Western countries. 6,[11][12][13] In many countries, TAVI can be performed in the cardiac catheterization laboratory, as well as in the hybrid operation room, according to guidelines or consensus documents. 14 Furthermore, the feasibility and safety of TAVI performed in the cardiac catheterization laboratory have been widely reported.…”
Section: Frequency Of Urgent/emergency Tavimentioning
confidence: 99%